Availability and Use of Reference Services and Resources by Undergraduates in Nigeria Maritime University Library - Ashima, Onajite Carol; Okoledo, Ejiro Princess; Ogoyibo, Hannah O. (Communicate: Journal of Library and Information Science, 2023)
This study investigated the availability and use of reference resources and services by undergraduates in Nigeria Maritime University Library. The study adopted the descriptive survey design and 334 undergraduates were randomly sampled from a population of 2000. Data collected were analysed using descriptive statistics. Findings revealed that there are various reference resources available to users with dictionary being the most available and used by undergraduate, majority of undergraduates use reference resources for personal research, most undergraduates use map & atlas and glossary twice monthly and power supply as a major challenges encountered by undergraduates in assessing reference resources and services in Nigeria maritime university library. The library management should therefore organize library orientation for incoming students to acquaint themselves with the available references resource and services and how to use them effectively.